Crossed sector automatic detection in 4G Radio Access Networks - Martins, A. (2019)
The Long Term Evolution (LTE) is the latest step in the advancing series of mobile telecommunications systems, it is called the fourth Generation (4G). In order to boost performance and deal with the increasing complexity within the operating 3G/4G networks, the Self-Organizing Networks (SON) concept was introduced.